Modeling User Interface Design E-Business Applications for Marketing Umkm Products in Payakumbuh City Using Pieces Framework - Rabby Nazli; Amrizal Amrizal; Hendra Hendra; Syukriadi Syukriadi (Universitas Islam Kuantan Singingi, 2024)
Micro, Small and Medium Enterprises (MSMEs) are productive economic enterprises that make a very significant contribution to the process of spurring the development of Indonesia's economic growth. On the one hand, the development of information technology is also growing very quickly. Therefore, managing micro, small and medium enterprises (MSMEs) businesses by utilizing digital technology is now an important part of increasing the competitiveness of micro ,small and medium enterprises (MSMEs) so that they are able to compete with other industry players. The aim of this research is to design an e-business design that can be used to improve business development performance in order to achieve its competitive targets so that it is able to compete with competitors in Payakumbuh city MSMEs. The framework used to analyze design feasibility tests is the PIECES Framework, which includes performance, information, economics, control, efficiency, and services. This method is used to measure the level of satisfaction with using the e-business system in managing MSME businesses in the city of Payakumbuh. The results of this research are in the range 3.4 – 4.91 = satisfied, so the design of the Payakumbuh City MSME e-business application is suitable for implementation in an application form that can be used by Payakumbuh City MSMEs and later used for testing the developed e-business system.